Legal Influences on Pension Trust Accounting. - Cramer, Joe J. (The Accounting Review, 1965)
The article discusses the overwhelming influence of legal documents on pension trust accounting and report preparation. The term pension trust is used in the conventional manner to refer to an arrangement whereby a corporation deposits contributions to pay pensions with a trustee, usually a bank or trust company. The discussion does not relate to insured pension plans because benefits under such plans are, in effect, guaranteed by the insurance company to the extent that corporation makes the agreed upon premium payments. Since the pension trust is a form of self-insurance, actuarial science should heavily influence accounting and reporting procedures applicable to the trust. The two disciplines, accounting and actuarial science, must be integrated or combined to produce reports which disclose pension trust operations for a period of time and status as of any point in time. It is reasonable to assume that in the near future pension trust accountings will evidence a long-run flavor based on general applicability of the entity concept and enterprise continuity to the trust. Only then will sufficient recognition be given the boundaries of entities, the corporation and the pension trust.